Analisis Ketersediaan Serta Situasi dan Kebutuhan Konsumsi Pangan Hewani Kabupaten Pangandaran : The Analysis of Availability, Situation and Consumption Needs of Animal-based Food in Pangandaran District - Firdaus, Robby Akmal; Heryatno, Yayat; Aries, Muhammad (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2023)
Availability of sufficient food can affect consumption and nutritional adequacy. Regions with high food availability will provide better nutritional adequacy and food consumption diversity. The direct cause of nutritional problems was the lack of food consumption. Lack of nutritional intake, especially those sourced from animal food, was one of the direct causes of increasing nutritional problems in an area. This research aimed to analyze the availability, situation and animal food consumption needs in Pangandaran District. This research used descriptive explanatory and prospective study design while the data was secondary data from related officials in Pangandaran district. The results showed that Pangandaran district in 2019 had the availability of animal food production, which was 46.5 g/cap/day. The contribution of the energy adequacy level (TKE) from the availability of animal food production was 29.4% and the contribution to the protein adequacy level (TKP) from the availability of animal food production was 42.6%. TKE and TKP from animal food consumption were 106.5% and 167.4% with score of desirable dietary pattern (PPH) was 24. To achieve the ideal PPH score, the target for animal food consumption in 2020-2024 is expected to have a declining growth rate of 1.25% per year. To meet the consumption target, it is necessary to have a growth rate of -0.25% per year to fulfill the need for animal food consumption in the same period. If the animal food consumption needs are only fulfilled from production, then there is still a gap in sufficed the animal food consumption needs of around 32.9 kg/cap/year or 14.53 thousand tons/year.